Factors affecting intra‐oral pH – a review. (30th August 2016) - Loke, C.; Lee, J.; Sander, S.; Mei, L.; Farella, M.
Summary: One of the greatest challenges to modern dentistry is the progressive destruction of tooth material due to chemical erosion. Dental erosion is the loss of dental hard tissue, without the action of bacteria, in which demineralisation of enamel and dentine results due to a decrease in intra‐oral pH. The aim of this review was to appraise the scientific literature on the factors that can affect intra‐oral pH. The review will examine (i) the protective role of human saliva, in terms of its mineral composition, flow rates and buffering systems and (ii) sources of in‐mouth acids such as extrinsic acids, which are derived from the diet and environment, as well as intrinsic acids, which are related to disorders of the gastro‐oesophageal tract. This review may assist clinicians to identify the risk factors for tooth wear and to recommend adequate preventive measures to patients.